2009
DOI: 10.1007/s11240-009-9621-z
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis and transformation of the diploid Rosa chinensis cv Old Blush

Abstract: International audienceSomatic embryogenesis was induced from in vitro-derived leaf explants of Rosa chinensis cultivar (cv) Old Blush. Calli producing embryos with expanded cotyledons (RcOBType1 embryos) were obtained. Further refinements of the callus maintenance medium generated a more typical rose embryogenic callus (RcOBType2) displaying high levels of secondary embryogenesis and embryos with limited cotyledon expansion Agrobacterium tumefaciens-mediated transformation assays using β-glucuronidase (GUS) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 31 publications
(46 reference statements)
0
30
0
Order By: Relevance
“…1) contains CaMV 35S promoter driven GUS gene interrupted by a modified castor bean catalase intron and CaMV 35S promoter driven hpt II gene conferring resistance to hygromycin. The intron within the GUS gene prevents its expression by Agrobacterium and allows the detection of eukaryotic expression only (Vergne et al 2010).…”
Section: Sensitivity Of Shoot Apices Of Pearl Millet To Hygromycinmentioning
confidence: 99%
“…1) contains CaMV 35S promoter driven GUS gene interrupted by a modified castor bean catalase intron and CaMV 35S promoter driven hpt II gene conferring resistance to hygromycin. The intron within the GUS gene prevents its expression by Agrobacterium and allows the detection of eukaryotic expression only (Vergne et al 2010).…”
Section: Sensitivity Of Shoot Apices Of Pearl Millet To Hygromycinmentioning
confidence: 99%
“…Use of alternative plant growth regulators, such as zeatin (Vergne et al 2009) to produce more transgenic China Rose lines, and using higher concentrations of cefotaxime to avoid contamination by Agrobacterium, will be assayed. The function of downstream genes controlled by MtDREB1C associated with freezing stress tolerance in the transgenic China Rose should also be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…For improvement of these traits in existing rose cultivars and species, genetic transformation is an important tool as it is well suited for specific improvement of individual traits without losing the existing rose characters 11 . Working on the transformation protocols, Firoozabady et al 12 first reported transformation based upon infection by A. tumefaciens in hybrid tea rose cultivar Royality.…”
Section: Rose (Rosa Hybrida)mentioning
confidence: 99%
“…Later, many researchers have reported this method as useful for rose transformation -based upon co-cultivation of friable embryogenic tissues with A. tumefaciens or A. rhizogenes for genes controlling flower colour 13 ; based on PEG-mediation using GFP as reporter gene 14 ; to enhance flower yield, resistance and essential oil 15 ; using embryogenic calluses and green florescent protein 5, gfp gene in rose cultivar 'Tineke' 16 and using somatic embryos in Rosa chinensis cv. Old Bush 11 . According to Merchant 17 , electrofusion was effective for the production of rose heterokaryons from protoplasts of four English rose cultivars, with a maximum fusion frequency of 1.62%.…”
Section: Rose (Rosa Hybrida)mentioning
confidence: 99%